Production of polyhydroxybutyrate and alginate from glycerol by Azotobacter vinelandii under nitrogen-free conditions - Yoneyama, Fuminori (Bioengineered, 2015)
Glycerol is an interesting feedstock for biomaterials such as biofuels and bioplastics because of its abundance as a by-product during biodiesel production. Here we demonstrate glycerol metabolism in the nitrogen-fixing species Azotobacter vinelandii through metabolomics and nitrogen-free bacterial production of biopolymers, such as poly-d-3-hydroxybutyrate (PHB) and alginate, from glycerol. Glycerol-3-phosphate was accumulated in A. vinelandii cells grown on glycerol to the exponential phase, and its level drastically decreased in the cells grown to the stationary growth phase. A. vinelandii also overexpressed the glycerol-3-phosphate dehydrogenase gene when it was grown on glycerol. These results indicate that glycerol was first converted to glycerol-3-phosphate by glycerol kinase. Other molecules with industrial interests, such as lactic acid and amino acids including γ-aminobutyric acid, have also been accumulated in the bacterial cells grown on glycerol. Transmission electron microscopy revealed that glycerol-grown A. vinelandii stored PHB within the cells. The PHB production level reached 33% per dry cell weight in nitrogen-free glycerol medium. When grown on glycerol, alginate-overproducing mutants generated through chemical mutagenesis produced 2-fold the amount of alginate from glycerol than the parental wild-type strain. To the best of our knowledge, this is the first report on bacterial production of biopolymers from glycerol without addition of any nitrogen source.